Comparison of the effectiveness of orthotic intervention, kinesiotaping, and paraffin treatments in patients with carpal tunnel syndrome: A single-blind and randomized controlled study - AKYÜZ, GÜLSEREN DERYA; YAĞCI, İLKER (HANLEY & BELFUS-ELSEVIER INC, 2019)
Purpose: The aim of the study was to compare different conservative treatments in patients with carpal tunnel syndrome (CTS). Study Design: A single-blind randomized controlled study. Methods: Patients (n = 169) diagnosed with mild or moderate CTS were screened; 110 met study requirements. The patients were randomized into 3 groups. The control (CON) comparison provided to all patients was a fabricated night orthotic which held the wrist in a neutral position. The second group received adjunctive kinesiotaping (KIN) and the third group received paraffin (PARA). All patients were evaluated clinically, electrophysiologically, and ultrasonographically before treatment and at 3 weeks, 3 months, and 6 months. Results: There were 36 patients in CON, 37 in KIN, and 37 in PARA. Pain reduction in KIN was better than the other groups at 3 weeks (mean difference [MD] in CON 2.4 +/- 2.5, KIN 3.7 +/- 2.0, PARA 2.7 +/- 2.3; P < .01) and 6 months (MD in CON 3.4 +/- 3.0, KIN 4.9 +/- 3.1, PARA 3.7 +/- 2.9: P < .05). KIN pain reduction was better than CON at 3 months (MD in CON 3.8 +/- 2.8, KIN 5.0 +/- 2.5: P <.05). Reduction of the cross-sectional area of median nerve at the level of radioulnar joint was greater for KIN than CON at 3 weeks (MD in CON 0.0 +/- 0.5, KIN 0.3 +/- 0.7; P < .01) than PARA at 3 months (MD in KIN 0.3 +/- 0.8, PARA 0.0 +/- 0.8; P < .05) and both groups at 6 months (MD in CON 0.1 +/- 0.8, KIN 0.5 +/- 0.9, PARA 0.0 +/- 1.0 P < .05). Conclusion: Adding KIN to night use of an orthotic was more effective in achieving symptomatic and structural improvements than either the orthotic alone or adjunctive use of paraffin in patients with mild and moderate CTS. (C) 2018 Hanley & Belfus, an imprint of Elsevier Inc. All rights reserved.
Keywords: Carpal tunnel syndrome; Orthotic; Kinesiotaping; Paraffin; Ultrasonography; FUNCTIONAL STATUS; SEVERITY; FIBERS